СОЦІАЛЬНО-ПСИХОЛОГІЧНІ ЧИННИКИ ЕФЕКТИВНОСТІ СИСТЕМИ МЕНЕДЖМЕНТУ ОРГАНІЗАЦІЇ - Антохов, Андрій; Клевчік, Леонід; Luste, Elena (My University, 2022)
The article examines the problems of inertia of institutional transformations and organizational changes in domestic conditions. Sources of institutional traps are analyzed. The role of changing management models in overcoming these problems is highlighted. Special importance is attached to the creation of an organizational culture based on trust, as well as to the transfer of emphasis in management from exclusively material aspects to the formation of the intellectual capital of the enterprise. The importance of taking into account the structural components of the national economic mentality in the formation and development of social capital as a factor of organizational changes and adaptability of the personnel management system is substantiated, the peculiarities of the economic mentality as an informal institution are determined, and the prospects for further research of this issue are outlined.
SOCIO-PSYCHOLOGICAL FACTORS OF THE EFFECTIVENESS OF THE ORGANIZATION'S MANAGEMENT SYSTEM
Keywords: стратегічний менеджмент; організаційна культура; самоменеджмент; економічний вибір; соціальний капітал; strategic management; organizational culture; self-management; economic choice; social capital